An autopsy case of Alzheimer's disease with amygdala‐predominant Lewy pathology presenting with frontotemporal dementia‐like psychiatric symptoms. Issue 2 (2nd February 2022) - Beck, Goichi; Shigenobu, Kazue; Ukon, Koto; Yamashita, Rika; Yonenobu, Yuki; Morii, Eiichi; Hasegawa, Masato; Ikeda, Manabu; Murayama, Shigeo; Mochizuki, Hideki
Abstract : Alzheimer's disease (AD) and frontotemporal dementia (FTD) are progressive neurodegenerative diseases associated with several cognitive and behavioral symptoms. It is sometimes difficult to distinguish AD from FTD in a patient because both of them can exhibit clinical overlap. In the present study, we report a case of a patient who showed sychiatric symptoms mimicking the behavioral variant of FTD (bvFTD) and combined AD amygdala‐predominant Lewy pathologies on autopsy. The patient was a Japanese man who developed personality changes in his late 50s, presenting with obsessive‐compulsive stereotypical behavior, stereotypy of speech, behavioral disinhibition, inertia, loss of empathy or sympathy, change in eating habits, and stimulus‐bound behavior. He also frequently left during medical examinations. Eventually, he was clinically diagnosed as having possible bvFTD, according to the International Consensus Criteria for bvFTD. The patient died of systemic metastasis of gastric cancer at 69 years of age. Postmortem neuropathological examination revealed severe AD pathology (Braak Amyloid stage C, Consortium to Establish a Registry for Alzheimer's Disease [CERAD] stage C, Thal phase 5, and Braak AT8 stage IV) along with Lewy pathology and argyrophilic grains, predominantly in the amygdala. Furthermore, no transactivation response DNA‐binding protein of 43 kDa (TDP‐43) pathology was observed. Our results suggest that a combination of these pathologies causes bvFTD‐like cognitive and behavioral symptoms. This case is very insightful when considering the lesions responsible for the psychiatric symptoms characteristic of bvFTD.